If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1g + 9 = 8g Reorder the terms: 9 + -1g = 8g Solving 9 + -1g = 8g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-8g' to each side of the equation. 9 + -1g + -8g = 8g + -8g Combine like terms: -1g + -8g = -9g 9 + -9g = 8g + -8g Combine like terms: 8g + -8g = 0 9 + -9g = 0 Add '-9' to each side of the equation. 9 + -9 + -9g = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -9g = 0 + -9 -9g = 0 + -9 Combine like terms: 0 + -9 = -9 -9g = -9 Divide each side by '-9'. g = 1 Simplifying g = 1
| 6y=7y+9 | | 16x-(1/x)=0 | | 5z=3z-4 | | 8+x=28+x | | 9-c=2c | | W-10/-2=0 | | 4c-2=18 | | 2x+12=-3x+5 | | Y=9/8x | | 2(z+-13)=-12 | | 5xa-12xa=-35 | | X+8=28+X | | 4y+8=3y | | 6q+2r-q+7r= | | -9d-4d=15 | | 129+191=n | | 10h-5h-4=6 | | 5a-12a=-35 | | 3x(3x-2)-4x(3x+4)= | | 13x+26=6x+180 | | 8q-5q= | | 9c-8=1 | | 2x-x=24-2x | | 20d-18d=2 | | 9y-6=-456 | | 7g=4 | | 17d-15d=20 | | 4n-6=94 | | x/4=3/4 | | 5x(2x+3)-2x(2x-1)= | | 2x-1/5=1 | | h=-16t^2+60t+2 |